THE RUSSIAN FEDERATION PROPAGANDA NARRATIVES - Karpchuk, Nataliia (Torun International Studies, 2021)
The article seeks to research the propaganda narratives of the Russian Federation in Europe. The Russian Federation has a long “successful” history of creating propaganda narratives since Soviet times. Even today, it spreads national and grand narratives to influence the external and internal audience. The narrative method is used to analyse both the content and the structure of the stories. The author makes the conclusion that the main purpose of Russia’s propaganda narratives is to convince its citizens and the whole world of Russia’s indomitable greatness and power, as well as to demonstrate the degradation of Europe and the West in general. To form the image of an invincible fighter for Christian values, the only outpost of stability, development, security (at least in Europe), Russia promotes a grand narrative, which is disseminated through daily disinformation, fakes and propaganda messages. The article finds out how the EU counteracts these destructive influences, specifically owing to the activity of the EUvsDisinfo site.